Factors Affecting Supply and Demand in The Automobile Industry of The Republic of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
The article considers the history of the existence of the national automotive industry. The main attention was paid to the formation of national and foreign automobile companies on the territory of the Republic of Uzbekistan, and an analysis was made of foreign motor transport manufacturers in the world. The factors of formation of supply and demand in the automotive market, as well as an analysis of world production and national output in recent years, have been studied. Problems are considered and proposals for solutions in this industry are given.